EUPATI Guidance for Patient Involvement in Medicines Research and Development: Health Technology Assessment - Hunter, Amy; Facey, Karen; Thomas, Victoria; Haerry, David; Warner, Kay; Klingmann, Ingrid; May, Matthew; See, Wolf (Frontiers in Medicine, 2018)
The main aim of health technology assessment (HTA) is to inform decision making by health care policy makers. It is a systematic process that evaluates the use of health technologies and generally involves a critical review of international evidence related to clinical effectiveness of the health technology vs. the best standard of care. It can also include an evaluation of cost effectiveness, and social and ethical impacts in the local health care system. The HTA process advises whether or not a health technology should be used, and if so, how it is best used and which patients are most likely to benefit from it. The importance of patient involvement in HTA is becoming widely recognized, for scientific and democratic reasons. The extent of patient involvement in HTA varies considerably across Europe. Commonly HTA is still focused on quantitative evidence to determine clinical and/or cost effectiveness, but the interest in understanding patients' experiences and preferences is increasing. Some HTA bodies provide support for participation in their processes, but again this varies widely across Europe. The involvement of patients in HTA is determined at the national and regional level, and is not subject to any European-wide legislation. The guidance text presented in this article was developed as part of the work of the European Patients' Academy on Therapeutic Innovation (EUPATI) and covers the interaction between HTA bodies and patients and their representatives when medicines are being assessed. Other EUPATI guidance documents relate to patient involvement in pharmaceutical industry-led research and development, ethics committees, and regulatory authorities. The guidance provides recommendations for activities to support patient involvement in HTA bodies and specific guidance for individual HTA processes. It seeks to improve patient involvement, using the outcomes of published research and consensus-building exercises. It also draws on good practice examples from individual HTA bodies. The guidance is not intended to be prescriptive and should be used according to specific circumstances, national legislation, or the unique needs of each interaction. This article represents the formal publication of the HTA guidance text with discussion about recent progress in, and continuing barriers to, patient involvement in HTA.